2018
DOI: 10.21451/1984-3143-ar2018-0095
|View full text |Cite
|
Sign up to set email alerts
|

Parthenogenetic bovine embryos secrete type I interferon capable of stimulating ISG15 in luteal cell culture

Abstract: Interferon tau (IFNT) is the pregnancy recognition signal in ruminants and is secreted by trophoblast cells. Paracrine action in the endometrium is well established by inhibiting luteolytic pulses of prostaglandin F2 alpha. Recently, endocrine action was documented in the corpus luteum, blood cell and liver. It was hypothesized that conditioned medium (CM) obtained from days 7, 9 and 12 parthenogenetic embryos alters luteal cell gene expression. The aim was to establish a bovine mixed luteal cell culture to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The main pathways changed by the embryo included type I interferon-response and genes associated to the prostaglandin metabolism. In agreement, recent in vitro studies showed that early bovine embryos were able to modulate gene expression of co-cultured endometrial 1012 , oviductal 13 , luteal 14 and immune cells 10,15,16 . However, a critical unanswered question is whether the female tract has the ability to respond to pre-hatching embryo-derived signals beyond the transcription level, to change its transport and secretory functions and ultimately change the composition of the uterine microenvironment.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…The main pathways changed by the embryo included type I interferon-response and genes associated to the prostaglandin metabolism. In agreement, recent in vitro studies showed that early bovine embryos were able to modulate gene expression of co-cultured endometrial 1012 , oviductal 13 , luteal 14 and immune cells 10,15,16 . However, a critical unanswered question is whether the female tract has the ability to respond to pre-hatching embryo-derived signals beyond the transcription level, to change its transport and secretory functions and ultimately change the composition of the uterine microenvironment.…”
Section: Introductionsupporting
confidence: 83%
“…Accumulating evidence supports the idea that the early bovine embryo is more than a passive passenger through the maternal reproductive tract. Embryo-induced effects, at transcriptional level, on oviductal 13 , endometrial 912 , luteal 14 and immune 15,16 cells have been reported. In the present study, we further advanced the understanding of the embryo effects in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…An important point in IFN-τ signaling is its capability to leave the uterine lumen and acts on distant tissues in an endocrine fashion. The endocrine effects of IFN-τ were confirmed by the expression of ISG in the liver (Meyerholz et al, 2015), luteal cells (Kiyma et al, 2016;Bridi et al, 2018) and immune cells in the bloodstream (Yankey et al, 2001;Hyungchul et al, 2006;Gifford et al, 2007;Kizaki et al, 2013;Pugliesi et al, 2014). Despite the fact that, no antiviral activity was detected in the main vessels (jugular) of the circulatory system.…”
Section: Autocrine Endocrine and Paracrine Actions Of Interferon-taumentioning
confidence: 97%
“…In the uterus, IFNT acts in a paracrine way, decreasing estrogen and oxytocin receptor expression in the endometrium, which is an essential step to maintaining a viable corpus luteum and producing progesterone [33]. Besides antiluteolytic function, IFNT has endocrine effects, stimulating the expression of IFN-stimulated genes (ISGs) in the endometrium [34], in the corpus luteum [35][36][37], in white blood cells [38], and in the liver [39]. The effects of IFNT secreted by the bovine embryo in the maternal organism can be detected as early as day 7 of development [40,41].…”
Section: Embryo-maternal Interactions Mediated By Embryotropinsmentioning
confidence: 99%